2022
DOI: 10.1088/1755-1315/1024/1/012060
|View full text |Cite
|
Sign up to set email alerts
|

Physical, milling quality and physicochemical characteristics of local rice cultivars from South Kalimantan, Indonesia

Abstract: Currently, local rice cultivars have not been used optimally and often experience extinction.The purpose of this study is to examine the physical quality, milling quality and physicochemical characteristics of several local rice cultivars from South Kalimantan. The research materials were obtained from plantings in the Sukamandi experimental field, where the seeds came from farmers in South Kalimantan and the quality examination are carried out at Rice Quality Laboratory in Indonesian Center for Rice Research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Whole rice grains are rice grains that are not broken and expressed as percentages (Müller, A., Nunes, M. T., Maldaner, V., Coradi, P. C., Moraes, R. S. de, Martens, S., Leal, A. F., Pereira, V. F., & Marin, C. K., 2022; Scariot, M. A., Karlinski, L., Dionello, R. G., Radünz, A. L., & Radünz, L. L., 2020) so that they have the best quality of rice and have a negative correlation with grains of broken and groats (Indrasari, S. D., Apriyati, E., Purwaningsih, H., Ardhiyanti, S. D., Kusbiantoro, B., Wening, R. H., & Usyati, N., 2022;Sulistyo, A., Mubarak, A., & Hendris, 2021). Figure 1 shows that the drying of 12 hours with a dryer resulted in the percentage of whole rice grains being 96.61%.…”
Section: Resultsmentioning
confidence: 99%
“…Whole rice grains are rice grains that are not broken and expressed as percentages (Müller, A., Nunes, M. T., Maldaner, V., Coradi, P. C., Moraes, R. S. de, Martens, S., Leal, A. F., Pereira, V. F., & Marin, C. K., 2022; Scariot, M. A., Karlinski, L., Dionello, R. G., Radünz, A. L., & Radünz, L. L., 2020) so that they have the best quality of rice and have a negative correlation with grains of broken and groats (Indrasari, S. D., Apriyati, E., Purwaningsih, H., Ardhiyanti, S. D., Kusbiantoro, B., Wening, R. H., & Usyati, N., 2022;Sulistyo, A., Mubarak, A., & Hendris, 2021). Figure 1 shows that the drying of 12 hours with a dryer resulted in the percentage of whole rice grains being 96.61%.…”
Section: Resultsmentioning
confidence: 99%
“…Indrasari et al. (2022) found that the head rice rate of the Kencana Baliman cultivar was 70.04%. Our results consist of Indrasari et al.…”
Section: Resultsmentioning
confidence: 99%
“…The percentage of rice varieties meet the Grade III national standard for head rice rate (GB/T 1354-2018). Indrasari et al (2022) found that the head rice rate of the Kencana Baliman cultivar was 70.04%. Our results consist of Indrasari et al (2022).…”
Section: Milling Qualitymentioning
confidence: 98%